Developing professional competencies and adaptability in modern-day students - Avazova, Feruza Bahodirovna (The Lingua Spectrum, 2026)
The article examines the formation of professional competencies and adaptability of students within the framework of the modern educational paradigm. The author analyzes the transition from a traditional explanatory-reproductive teaching model to a system-activity approach, where the central role is assigned to the student’s independent cognitive activity. Special attention is paid to the need for developing “soft skills” and the ability to rapidly adapt within a dynamic information environment. The paper substantiates the teacher’s role as a mentor who facilitates the student’s creative potential, as well as the importance of implementing information and communication technologies to create personalized educational trajectories.